Analisis Keterampilan Berpikir Kritis dan Kreatif dalam Pembelajaran Pendidikan Pancasila pada Program Sekolah Dasar Penggerak - Berlianisa, Kumala; Winarno; Purnama Adi, Fadhil (Jurnal Dikdas Bantara, 2025)
This study aims to describe the implementation of critical and creative thinking skills in Pancasila Education learning at Penggerak Elementary School with a focus on Phase B. This study uses a qualitative approach with a case study method, and data are presented descriptively through observation, interviews, and documentation. The results of the study indicate that the planning for the implementation of critical and creative thinking skills has been structured in the teaching module. During the implementation, teachers apply active learning strategies such as group discussions and presentations that successfully involve students actively and facilitate the development of critical and creative thinking skills. Evaluation of the implementation of critical and creative thinking skills is not only seen from learning outcomes, but teachers also assess the learning process and reflection of students. Pancasila Education learning does not only emphasize mastery of content, but also the formation of critical and creative thinking patterns. This study provides recommendations for teachers to continue developing student independence in thinking and documenting the learning process more systematically to support improving the quality of learning in the future.